A rare cause of gastrointestinal bleeding in adults: Ileal duplication with ulceration: A case report and review of literature - Li, Lingli; Li, Hongping; Chen, Xiaoyan; Yao, Jin; Xie, Rui; Wang, Hong (Frontiers in Surgery, 2022)
The ileal duplication, which is a congenital anatomical abnormality of the digestive tract, can lead to the manifestation of the alimentary tract duplication in the small intestine. It is also the rare cause of gastrointestinal bleeding and usually seen in infants, but only rarely in adults. Herein, we describe a case of adult male was suffering from intermittent massive hematochezia for three years, accompanied by abdominal pain, syncope, and palpitations. However, no positive findings were found by gastroscopy and colonoscopy in other hospitals. He visited our hospital owing to the recurrent hematochezia, but re-examination by gastroscopy and colonoscopy indicated no significant abnormality, and hence small intestinal vascular malformation bleeding was considered. Therefore, double-balloon enteroscopy (DBE) examination was conducted and the results revealed a double-lumen opening in the ileum, which was 100 cm from the ileocecal valve. The blind end was observed 6 cm away from one opening along the depth direction, and an ulcer was observed on the intestinal wall of the blind segment, which was considered as an ileal duplication. The patient thereafter underwent surgery subsequently. Postoperative pathology confirmed ileal duplication and that gastrointestinal bleeding was primarily caused by ulcer hemorrhage. The patient had no discomfort after the follow-up. In this report, we have reviewed and summarized the literature to provide references for both diagnosis and treatment of ileal duplication.